Economic and humanistic burden associated with noncommunicable diseases among adults with depression and anxiety in the United States. (1st September 2020) - Armbrecht, Eric; Shah, Anuj; Schepman, Patricia; Shah, Ruchit; Pappadopulos, Elizabeth; Chambers, Richard; Stephens, Jennifer; Haider, Seema; McIntyre, Roger S.
Abstract: Aims: This study estimated the economic and humanistic burden associated with chronic non-communicable diseases (NCCDs) among adults with comorbid major depressive and/or any anxiety disorders (MDD and/or AAD). Materials and methods: A retrospective analysis was conducted using the Medical Expenditure Panel Survey data (2010–2015). The analytic cohort included adults (≥18 years) with MDD only (C1), AAD only (C2), or both (C3). The presence of either of 6 NCCDs (cardiovascular diseases [CVD], pulmonary disorders [PD], pain, high cholesterol, diabetes, and obesity) were assessed. Study outcomes included healthcare costs, activity limitations, and quality of life. Multivariate regressions were conducted in each of the 3 cohorts to evaluate the association between the presence of NCCDs and outcomes. Results: The analytic sample included 9, 160, 465 patients: C1 (4, 391, 738), C2 (3, 648, 436), C3 (1, 120, 292). Pain (59%) was the most common condition, followed by CVD (55%), high cholesterol (50%), obesity (42%), PD (17%), and diabetes (14%). Mean annual healthcare costs were the greatest for C3 ($14, 317), followed by C1 ($10, 490) and C2 ($7, 906). For C1, CVD was associated with the highest increment in annual costs ($3, 966) followed by pain ($3, 617). For C2, diabetes was associated with the highest incremental annual costs ($4, 281) followed by PD ($2, 997). For C3, cost trends were similar to those seen in C2. NCCDs resulted in a significant decrease in physical quality of life across all cohorts. Pain was associated with a significantly higher likelihood of self-reported physical, social, cognitive, and activity limitations compared to those without pain. Conclusions: 60% of patients with MDD and/or AAD had at least one additional NCCD, which significantly increased the economic and humanistic burden. These findings are important for payers and clinicians in making treatment decisions. These results underscore the need for development of multi-pronged interventions which aim to improve quality of life and reduce activity limitations among patients with mental health disorders and NCCDs.